Phenotypic spectrum and long-term outcomes of patients with 46,XX disorders of sex development - Heeyon Yoon; Dohyung Kim; Ja Hye Kim; Han-Wook Yoo; Jin-Ho Choi (Annals of Pediatric Endocrinology & Metabolism)
Purpose 46,XX disorders of sex development (DSD) involve atypical genitalia accompanied by a normal female karyotype. This study was performed to investigate the clinical characteristics and long-term outcomes of patients with 46,XX DSD. Methods The study included 34 patients with 46,XX DSD who presented with ambiguous genitalia or delayed puberty. Patients with congenital adrenal hyperplasia were excluded. Clinical phenotypes and overall outcomes were analyzed retrospectively. Results Age at presentation ranged from birth to 40 years (median, 0.6 years), and the follow-up period ranged from 0.3 to 29.7 years (median, 8.8 years). Twenty patients were assigned female (58.8%). Etiologies included disorders of gonadal development (n=22), exogenous androgen exposure during pregnancy (n=5), association with syndromic disorders or genital anomalies (n=2), and unclassified causes (n=5). Ovotestis was the most frequent gonadal pathology (41.7%). Müllerian duct remnants were usually underdeveloped (52.9%) or absent (23.5%). Spontaneous puberty occurred in 17 of the 21 patients of pubertal age, while 9 patients required sex hormone replacement therapy. Gonadal complications were observed in 4 patients (gonadal tumors [n=3], and spontaneous gonadal rupture [n=1]), and gender dysphoria occurred in 1 patient who was assigned male. Conclusions This study described the wide phenotypic spectrum and pubertal outcome of patients with 46,XX DSD. Long-term multidisciplinary monitoring for pubertal development, fertility, gender identity, and gonadal complications is recommended.